Efektivitas Umpan Balik Konstruktif terhadap Pengembangan Soft Skill Mahasiswa Teknik Informatika - Titik Oktaviani; Rahmawati Rahmawati (Router : Jurnal Teknik Informatika dan Terapan, 2026)
Soft skills are essential competencies for Informatics Engineering students besides academic and technical abilities. One learning approach that supports soft skill development is the implementation of constructive feedback in the learning process. This study aims to analyze the effectiveness of constructive feedback in improving the soft skills of Informatics Engineering students, particularly in interpersonal communication, teamwork, self-confidence, and the ability to accept criticism positively. The research applied a descriptive qualitative method through literature studies and observations during interpersonal learning activities. Data were collected by observing classroom discussions, group assignments, and interactions among students. The findings indicate that constructive feedback provides positive contributions to the improvement of students’ communication skills, emotional control, and collaborative attitudes within teams. Students became more confident in expressing opinions and more open to receiving criticism and suggestions from others. In addition, the implementation of constructive feedback created a more active, supportive, and interactive learning environment. The results also show that constructive feedback helps students conduct self-evaluation and continuously improve their interpersonal skills. Therefore, constructive feedback is considered effective in supporting the development of soft skills among Informatics Engineering students in higher education environments.